Numerical simulation of temperature and relative humidity in zero energy cool chamber - Yanhua, Liu; Enli, Lyu; Rahman, Muhammad M.; Yu, Wang; Jiaming, Guo; Jie, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Temperature and relative humidity are important parameters that can affect the storage of food in a zero energy cool chamber (ZECC). The distributions of average temperature and relative humidity are influenced by factors such as chamber size, water temperature, load weight and filler thickness. In this research, thermal environment analysis using numerical simulation of biological respiration was conducted for tomatoes stored in a ZECC. The ZECC was composed of inner and outer brick walls, filler (a mixture of sand and zeolite), water between the walls and a shading curtain. The results obtained from the numerical model were compared by setting different values for each factor. The following conclusions are drawn after comparison and analysis of results: (1) the distributions of average temperature and relative humidity are strongly related to the thickness of the filler – a thicker filler causes a lower temperature; (2) the water temperature in the filler exerts little influence on the average temperature and relative humidity; and (3) the lowest temperature and the highest relative humidity can be achieved with a chamber size of 0.6 m and a load weight of 30 kg. In addition, to validate the results of the numerical model, the simulation results are compared with experimental data, which show good agreement. It is confirmed that numerical simulation can be satisfactorily applied to predict the distribution of environmental parameters such as temperature and relative humidity in a cool chamber. Keywords: zero energy cool chamber, numerical model, temperature, relative humidity DOI: 10.3965/j.ijabe.20171003.3050 Citation: Liu Y H, Lyu E L, Rahman M M, Wang Y, Guo J M, Zhang J. Numerical simulation of temperature and relative humidity in zero energy cool chamber. Int J Agric & Biol Eng, 2017; 10(3): 185–193.